2019
DOI: 10.1089/jmf.2018.4375
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effects of Dendropanax morbifera on Cognitive Impairment Via Enhancing Cholinergic Functions and Brain-Derived Neurotrophic Factor Expression in β-Amyloid-Induced Mice

Abstract: Alzheimer's disease accounts for the majority of dementia and shows hallmarks such as sequential cognitive dysfunction and abnormal behavior. Dendropanax morbifera (DM) has traditionally been used to treat a variety of diseases in East Asia. The aim of this study was to assess the therapeutic effects of DM on brain neuron damage and on cognitive deficit in neuronal cell induced by Ab1-42 in mice. Treatment with DM reduced the levels of intracellular reactive oxygen species and protected against the death of ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 38 publications
(44 reference statements)
0
6
0
Order By: Relevance
“…Natural compounds, such as β-Amyrin, were tested for ameliorating memory deficit and decreasing neurogenesis impairments in Aβ-injected AD mice models [106]. Similarly, Dendropanax morbifera was tested in Aβ peptide-treated mice in order to produce brain neuron damage and on cognitive deficit in neuronal cell, showing benefic effects [107] the same way Salicornia europaea L. administration demonstrated anti-neuroinflammatory and ameliorative potential in scopolamine-induced amnesic C57/BL6N mice [108]. These observations are also sustained by years of clinical expertise and observations.…”
Section: Different Preclinical Models To Study Cholinergic Hypothesismentioning
confidence: 99%
“…Natural compounds, such as β-Amyrin, were tested for ameliorating memory deficit and decreasing neurogenesis impairments in Aβ-injected AD mice models [106]. Similarly, Dendropanax morbifera was tested in Aβ peptide-treated mice in order to produce brain neuron damage and on cognitive deficit in neuronal cell, showing benefic effects [107] the same way Salicornia europaea L. administration demonstrated anti-neuroinflammatory and ameliorative potential in scopolamine-induced amnesic C57/BL6N mice [108]. These observations are also sustained by years of clinical expertise and observations.…”
Section: Different Preclinical Models To Study Cholinergic Hypothesismentioning
confidence: 99%
“…Overall, TPs have beneficial effects in protecting neurons from exogenous damage, such as STS-induced neurotoxicity and cell death. Moreover, EGCG also improved memory in PS2 mice by inhibiting ERK and NF- βB pathways to induce γ-secretase and β-secretase activity [ 115 ].…”
Section: Mechanisms Of the Neuroprotective Effect Of Tpsmentioning
confidence: 99%
“…In addition, rutin treatment modulated the Bax/Bcl-2 ratio, and caspase-3 activation and prevented apoptotic cell death. Finally, it was also observed that rutin effectively suppressed JNK and p38 MAPK signaling induced by rotenone [ 66 ].…”
Section: Medicinal Uses and Pharmacological Properties Of mentioning
confidence: 99%